A suppressive antagonism evidences Progesterone and Estrogen receptor pathway interaction with concomitant regulation of Hand2, Bmp2 and ERK during early decidualization - Mestre Citrinovitz, Ana Cecilia (2015)
Progesterone receptor and estrogen receptor participate in growth and differentiation of the different rat decidual regions. Steroid hormone receptor antagonists were used to study steroid regulation of decidualization. Here we describe a suppressive interaction between progesterone receptor (onapristone) and estrogen receptor (ICI182780) antagonists and their relation to a rescue phenomenon with concomitant regulation of Hand2, Bmp2 and p-ERK1/2 during the early decidualization steps. Phenotypes of decidua development produced by antagonist treatments were characterized by morphology, proliferation, differentiation, angiogenesis and expression of signaling molecules. We found that suppression of progesterone receptor activity by onapristone treatment resulted in resorption of the implantation sites with concomitant decrease in progesterone and estrogen receptors, PCNA, KI67 antigen, DESMIN, CCND3, CX43, Prl8a2, and signaling players such as transcription factor Hand2, Bmp2 mRNAs and p-ERK1/2. Moreover, FGF-2 and Vegfa increased as a consequence of onapristone treatment. Implantation sites from antagonist of estrogen receptor treated rats developed all decidual regions, but showed an anomalous blood vessel formation at the mesometrial part of the decidua. The deleterious effect of onapristone was partially counteracted by the impairment of estrogen receptor activity with rescue of expression levels of hormone steroid receptors, proliferation and differentiation markers, and the induction of a probably compensatory increase in signaling molecules Hand2, Bmp2 and ERK1/2 activation compared to oil treated controls. This novel drug interaction during decidualization could be applied to pathological endometrial cell proliferation processes to improve therapies using steroid hormone receptor targets.